2012
DOI: 10.1259/bjr/16327485
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and renoprotective effects of paricalcitol on experimental contrast-induced nephropathy model

Abstract: Objectives: The aim of the study was to assess the effect of paricalcitol on the experimental contrast-induced nephropathy (CIN) model. We hypothesised that paricalcitol may prevent CIN. Methods: 32 Wistar albino rats were divided into four groups (n58 each): control group, paricalcitol group, CIN group and paricalcitol plus CIN group. Paricalcitol (0.4 mg kg -1 day -1 ) was given intraperitoneally for 5 consecutive days prior to induction of CIN. CIN was induced at day 4 by intravenous injection of indometaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…Oxidative stress refers to the imbalance between the antioxidative defense system and the oxidative system [26,27]. Recently, it is documented that paricalcitol has not only renin inhibitor effects, but also antioxidant effects [12,28,29,30]. Izquierdo et al reported that paricalcitol decreases serum MDA levels and increases serum GSH, thioredoxin, catalase and SOD activities in hemodialysis patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress refers to the imbalance between the antioxidative defense system and the oxidative system [26,27]. Recently, it is documented that paricalcitol has not only renin inhibitor effects, but also antioxidant effects [12,28,29,30]. Izquierdo et al reported that paricalcitol decreases serum MDA levels and increases serum GSH, thioredoxin, catalase and SOD activities in hemodialysis patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Histological sections were evaluated by a board-certified veterinary pathologist who was blinded to the experimental groups at the time of evaluation. Histological alterations were evaluated by a modification of a previously described scoring system for evaluation of CIAKI [37] . This consisted of assessment for tubular damage and protein casts according to the following key: 0, no alterations; 1, mild, isolated foci, <5% tubules affected; 2, moderate, 5–25% tubules affected; 3, marked, 26–50% tubules affected; 4, severe, >50% tubules affected.…”
Section: Methodsmentioning
confidence: 99%
“…In a rat model of amikacin-induced nephrotoxicity, renal tissue MDA levels were significantly lower, and SOD and glutathione peroxidase activities in the kidney were significantly higher when rats were treated with paricalcitol [ 29 ]. Other reports have also proven the effects of paricalcitol on renal oxidative stress biomarkers, such as thiobarbituric acid-reactive substrates and 8-hydroxy-2′-deoxyguanosine, in models of contrast- or cyclosporine-induced nephropathy [ 30 31 ]. However, a previous study using a combined aliskiren and paricalcitol treatment showed no increased effect on oxidative stress of kidneys in a streptozotocin-induced diabetic model over that of either agent alone [ 32 ]; these results are consistent with our current findings in UUO.…”
Section: Discussionmentioning
confidence: 99%